ANALISIS EFISIENSI ALOKATIF PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHATANI JAGUNG (Zea mays L.) (Studi Kasus di Desa Bocek, Kecamatan Karangploso, Kabupaten Malang) - eka rahayu; Farida Syakir; Sri Hindarti (Program Studi Agribisnis, 2019)
AbstractThis study aims to analyze and find out the income of corn farming, knowing the effect of production factors on corn farming, knowing the allocative efficiency of the use of production factors in corn farming. This study was determined by purposive sampling in Bocek Village, Karangploso Subdistrict, Malang Regency using a randomized method using 36 samples of corn farmers. The analytical method used is the analysis of Cobb-Douglass production function and analysis of production input allocation efficiency (NPMx / Px). The results showed that the R / C ratio was 1.7 which means it was profitable and worth trying. Production factors that significantly influence corn farming are seeds, urea fertilizer, manure, pesticides and labor. Farmers in allocating their production inputs are not efficient, because the value of NPMx / Px of the five production factors is greater than 1. Therefore allocatively, the use of corn production factors is not efficient so that it needs to be added to its use. Keyword: factors, production, efficiency, allocative, income